Towards an integrated workforce management system - Landa-Silva, Dario; Castillo, Arturo; Bowie, Leslie; Johnston, Hazel (2010)
We describe progress towards a workforce management system in which personnel scheduling is integrated with other important processes such as payroll processing, attendance and absence recording, staffing forecast and planning, etc. Our focus is on customeroriented sectors in which a considerable proportion of the available workforce is part-time. First, we discuss the importance of having an integrated workforce management strategy and then, we address the particular aspects of shift pattern design and staff allocation using a fast-food restaurant and a leisure centre as examples.